The 3D Suite Computer Program - Daud, Abdullah (Fakulti Ukur dan Harta Tanah, 1990)
The 3D post processing suite or the 3Dsuite. Is a menu driven sortware written in fortran 77 language in purely geometrical three dimensional geodetic model using a rigorous least squares estimation technique for simultaneous orocessing of three categories of data as follows: